Prospective analysis of incidence, extent and chronicity of lower extremity venous thrombosis. (February 2014) - Poulikidis, K P; Gasparis, A P; Labropoulos, N
Objective: This study was designed to determine all variables related to lower extremity deep venous thrombosis (DVT) to be used as reference in patients examined in a hospital setting. Methods: Consecutive patients presented with signs and symptoms of venous thromboembolism over a one-year period, examined in our university hospital. Patients' demographics and clinical characteristics in a data base organized to answer all the pertinent questions. Results: There were 2594 patients. Thrombosis was found in 348 (13.4%) of which 249 were acute and 72 had chronic luminal changes. Unilateral thrombosis was found in 268 and bilateral in 80. Acute DVT and/or chronic changes were more common on the left limb. Chronic thrombosis was more prevalent in the proximal veins. Acute thrombosis was more often found in the inpatients. Both acute DVT and chronic changes were found in 27 patients (7.8%) of whom 15 were bilateral. Conclusions: Various patterns of thrombosis are found in both inpatients and outpatients with the former having a higher incidence of acute events. Acute, chronic and recurrent thrombosis are very frequent and very important to report as they could change the management of the patients.